Factors Influencing the Patient with Rheumatoid Arthritis in their Decision to Seek Podiatry. (24th January 2013) - Blake, A.; Mandy, P. J.; Stew, G .
Abstract Introduction Despite the level of foot involvement in rheumatoid arthritis (RA), and the literature to support early assessment of foot care needs, local referral of patients to podiatry has been occurring too late to instigate certain preventative interventions. Preliminary fieldwork has highlighted that the primary responsibility for the instigation of this lies with the patient. The present study describes the factors that influence the patient with RA in their decision to self‐report foot problems. Method A case study research strategy was employed. Nine patients attending the outpatient rheumatology department participated in the study and data were gathered through semi‐structured interviews. This information was analysed using a framework approach. Results The key themes derived from the data suggested that there are a variety of factors influencing the patient's decision to self‐report foot concerns. Some will act to encourage the action and others will act to oppose it. Other factors can influence the decision either way, depending on the individual patient (psychological state, previous experience, body image changes). In addition, age, gender, and cultural and social aspects are also significant. Conclusion Due to the multitude of factors influencing the individual's decision to seek help, the patient cannot be given sole responsibility for their foot health if we wish to achieve timely and appropriate podiatry, as recommended in the literature. Responsibility should be three‐way; the patient, the members of the rheumatology team and, once in the podiatry service, the podiatrist should maintain this. Copyright © 2013 John Wiley & Sons, Ltd.